Dose-adapted salvage radiotherapy after radical prostatectomy based on an erMRI target definition model: Toxicity analysis. (January 2014) - Zilli, Thomas; Jorcano, Sandra; Peguret, Nicolas; Caparrotti, Francesca; Hidalgo, Alberto; Khan, Haleem G.; Vees, Hansjorg; Weber, Damien C.; Miralbell, Raymond
Abstract: Background . To assess treatment tolerance by patients treated with a dose-adapted salvage radiotherapy (SRT) protocol based on an multiparametric endorectal magnetic resonance imaging (erMRI) failure definition model after radical prostatectomy (RP). Material and methods. A total of 171 prostate cancer patients recurring after RP undergoing erMRI before SRT were analyzed. A median dose of 64 Gy was delivered to the prostatic bed (PB) with, in addition, a boost of 10 Gy to the suspected relapse as visualized on erMRI in 131 patients (76.6%). Genitourinary (GU) and gastrointestinal (GI) toxicities were scored using the RTOG scale. Results. Grade ≥ 3 GU and GI acute toxicity were observed in three and zero patients, respectively. The four-year grade ≥ 2 and ≥ 3 late GU and GI toxicity-free survival rates (109 patients with at least two years of follow-up) were 83.9 ± 4.7% and 87.1 ± 4.2%, and 92.1 ± 3.6% and 97.5 ± 1.7%, respectively. Boost (p = 0.048) and grade ≥ 2 acute GU toxicity (p = 0.008) were independently correlated with grade ≥ 2 late GU toxicity on multivariate analysis. Conclusions. A dose-adapted, erMRI-based SRT approach treating the PB with a boost to the suspected local recurrence may potentially improve the therapeutic ratio by selecting patients that are most likely expected to benefit from SRT doses above 70 Gy as well as by reducing the size of the highest-dose target volume. Further prospective trials are needed to investigate the use of erMRI in SRT as well as the role of dose-adapted protocols and the best fractionation schedule.